Analisis Keuangan Inklusif dan Tingkat Kemiskinan Di Kabupaten Timor Tengah Utara - Nalle, Frederic; Felisisima Afoan (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
East Nusa Tenggara Province is one of the provinces with the largest poverty percentage in Indonesia after Papua and West Papua Provinces. The high percentage of the number of poor people in NTT Province, one of the biggest contributors comes from the North Central Timor Regency. The data released by the Central Statistics Agency noted that TTU Regency was the eighth (8) highest contributor to poverty out of 22 Regencies/Cities in the autonomous region of NTT Province. This study aims to determine the effect of the variable capital expenditures, balancing funds and Silpa funds on poverty in TTU Regency. The results showed that either partially or simultaneously each independent variable had a significant effect on poverty in TTU Regency.